Use of Teaching Games for Understanding in Team Sports in the Context of Physical Education: A Systematic Review; [Utilización del Teaching Games for Understanding en Deportes de Equipo en el Contexto de la Educación Física: Una Revisión Sistemática] - De Moraes-Ferrari, G (Didactic Asociation Andalucia, 2023)
The purpose of this work was to carry out a systematic review on the use of the Teaching Games for Understanding (TGfU) model and its hybridizations in team sports in the context of physical education. The process was carried out in the WOS database under the guidelines of the PRISMA methodology. The works were selected based on different inclusion and exclusion criteria, obtaining as a result 20 articles (10 TGfU and 10 TGfU/Hybrid) published in the last 5 years (2019-2023) in English and Spanish. These results were described and analyzed according to: authors and year of publication, country, sample/grade and duration, sport, objectives, method and instruments, variables, and results. Most of the studies are carried out in Spain. The sample is equally distributed between Primary and Secondary Education, although it also included high school students. The duration of the application of the methodology is consistent with the benefits obtained. The use of the TGfU is more frequent in traditional sports, despite including other team sports. The works were oriented to the analysis and comparison of psychosocial-affective variables, of physical performance and cognitive-motor performance of the game. The quantitative research method predominates, using questionnaires, observational tools, semi-structured interviews and focus groups as a measurement instrument. In conclusion, this review demonstrates the importance of both the TGfU and its hybridizations in the context of physical education with team sports, and may be useful for teachers and researchers in this field, contributing to the physical, cognitive, social and affective development of students. © 2023 Didactic Asociation Andalucia. All rights reserved.